2019
DOI: 10.1093/hmg/ddz010
|View full text |Cite
|
Sign up to set email alerts
|

The TFAP2A–IRF6–GRHL3 genetic pathway is conserved in neurulation

Abstract: Mutations in IRF6, TFAP2A and GRHL3 cause orofacial clefting syndromes in humans. However, Tfap2a and Grhl3 are also required for neurulation in mice. Here, we found that homeostasis of Irf6 is also required for development of the neural tube and associated structures. Over-expression of Irf6 caused exencephaly, a rostral neural tube defect, through suppression of Tfap2a and Grhl3 expression. Conversely, loss of Irf6 function caused a curly tail and coincided with a reduction of Tfap2a and Grhl3 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 65 publications
(96 reference statements)
5
34
0
Order By: Relevance
“…This leads us to speculate the existence of a threshold level for IRF6, somewhere between 0% and 50%, that is required for proper cell migration. The idea of threshold level has been previously reported for IRF6 in craniofacial development and more recently demonstrated for a new function of IRF6 in neurulation . Further studies could take advantage of the unique allelic combinations described in this latter study to define the required IRF6 level for epidermal migration.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This leads us to speculate the existence of a threshold level for IRF6, somewhere between 0% and 50%, that is required for proper cell migration. The idea of threshold level has been previously reported for IRF6 in craniofacial development and more recently demonstrated for a new function of IRF6 in neurulation . Further studies could take advantage of the unique allelic combinations described in this latter study to define the required IRF6 level for epidermal migration.…”
Section: Discussionmentioning
confidence: 51%
“…The idea of threshold level has been previously reported for IRF6 in craniofacial development 6,15 and more recently demonstrated for a new function of IRF6 in neurulation. 34 Further studies could take advantage of the unique allelic combinations described in this latter study to define the required IRF6 level for epidermal migration. Among the three syndromic cases with IRF6 mutations reported in this current study, we determined the genotype of two single nucleotide polymorphisms in IRF6 that are associated with NSCLP.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of cases are caused by mutations in IRF6 , which are also linked with dominant Popliteal pterygium syndrome (PPS), a condition that affects the skin and genitals and also frequently includes CL/P (Kondo et al, 2002). Mutations in Grainyhead‐like 3 ( GRHL3 ), an ectodermal IRF6 target (Kousa et al, 2019), were identified as the cause of many of the VWS cases in which no causative variant in IRF6 could be identified (Peyrard‐Janvid et al, 2014). Cytosolic IRF6 interacts with regulators of cytoskeletal remodeling and cell adhesion, nonmetastatic expressed 1 (NME1) and NME2.…”
Section: Genetics Of Human Ofcsmentioning
confidence: 99%
“…Complete loss of Tfap2a in mouse models causes severe developmental defects including anencephaly, facial clefts, and thoraco-abdominoschisis 34 . On some backgrounds, heterozygous null mutants exhibit anencephaly 35 . Although the human phenotype caused by TFAP2A mutations is considerably less severe 36 , Branchiooculofacial syndrome (BOFS) is described as a very rare disorder with less than 200 described cases as of 2019 37 , corresponding to an estimated prevalence between 1 in 300,000 and 1 in 1,000,000 individuals.…”
Section: Discussionmentioning
confidence: 99%